2016
DOI: 10.1080/08927014.2016.1164845
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and anti-biofilm activity of extracellular polymeric substances produced by the marine biofilm-forming bacteriumPseudoalteromonas ulvaestrain TC14

Abstract: This study investigated soluble (Sol-EPS), loosely bound (LB-EPS), and tightly bound extracellular polymeric substances (TB-EPS) harvested from biofilm and planktonic cultures of the marine bacterium Pseudoalteromonas ulvae TC14. The aim of the characterization (colorimetric methods, FTIR, GC-MS, NMR, HPGPC, and AFM analyses) was to identify new anti-biofilm compounds; activity was assessed using the BioFilm Ring Test®. A step-wise separation of EPS was designed, based on differences in water-solubility and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…More interestingly is the emulsifying activity of PE12, able to produce stable emulsions with various food oils even at very low concentration (0.02%). An anti-biofilm activity was revealed for a pool of polysaccharides isolated from Pseudoalteromonas ulvae strain TC14 grown in sessile conditions [ 102 ]. These polymers—named LB-EPS and TB-EPS depending on whether they are loosely or tightly bound to the cells—and the medium soluble EPS (Sol-EPS), inhibit the biofilm of some marine bacterial strains.…”
Section: Structure Of Exopolysaccharides (Epss) From Marine Bactermentioning
confidence: 99%
See 1 more Smart Citation
“…More interestingly is the emulsifying activity of PE12, able to produce stable emulsions with various food oils even at very low concentration (0.02%). An anti-biofilm activity was revealed for a pool of polysaccharides isolated from Pseudoalteromonas ulvae strain TC14 grown in sessile conditions [ 102 ]. These polymers—named LB-EPS and TB-EPS depending on whether they are loosely or tightly bound to the cells—and the medium soluble EPS (Sol-EPS), inhibit the biofilm of some marine bacterial strains.…”
Section: Structure Of Exopolysaccharides (Epss) From Marine Bactermentioning
confidence: 99%
“…Capsular polysaccharides are frequently found to be involved in adhesion processes and several EPS/CPS included in this review are reported to be “sticky”. This property is useful for both colonization [ 107 ] and for microbial-host interaction [ 62 , 63 , 102 ]. There is a body of evidence that a huge number of marine microorganisms are able to form biofilms [ 8 , 190 , 191 ].…”
Section: Structure-function Relationships and Ecological Rolementioning
confidence: 99%
“…For instance, K. pneumoniae capsular polysaccharide was suggested to restrict biofilm formation in several clinically important Gram-positive and Gram-negative bacterial species such as S. epidermidis , S. aureus , E. coli , and Enterobacter aerogenes [ 124 , 125 ]. Extracellular polymeric substances such as natural high molecular weight polymers secreted by bacteria have also been suggested to be anti-biofilm candidates [ 126 ]. Interruption of bacterial signaling systems such as quorum sensing affects bacterial biofilm formation.…”
Section: Promising Novel Therapies For Prevention and Treatment Ofmentioning
confidence: 99%
“…10 The contents of polysaccharide, protein and nucleic acid in EPS have a substantial effect on the occulation of bacteria. A large amount of work has been conducted on characterizing the EPS of various pure and mixed cultures, e.g., Pseudomonas sp., 11 Bacillus sp., 12 activated sludge, [13][14][15][16] granular sludge 17,18 and bio-lm 19,20 in wastewater treatment systems. However, little information is available on the characteristics of EPS of thermophilic aerobic denitrifying bacterium.…”
Section: Introductionmentioning
confidence: 99%